Influence of adhesive system on quartz fiber post dislocation resistance in endodontically treated teeth - Luis Francisco Maglione García; Vicente Castelo Branco Leitune; Stéfani Becker Rodrigues; Susana Maria Werner Samuel; Fabrício Mezzomo Collares (Universidade Estadual de Campinas, 2016)
Aim: To evaluate the dislocation resistance of the quartz fiber post/cement/dentin interface after different adhesion strategies. Methods: Forty bovine lower central incisors were selected and prepared with K-files using the step-back technique, and irrigated with 3 mL of distilled water preceding the use of each instrument. Prepared teeth were stored at 37ºC and 100% humidity for 7 days. The roots were prepared and randomized into 4 groups. The quartz fiber post was cemented with an adhesion strategy according to the following groups: GBisCem- BISCEM; GOneStep±C&B- One Step ± C&B; GAllBond±C&B- AllBond3 ± C&B; GAllBondSE±C&B- AllBondSE ±C&B with a quartz fiber post. Cross-sectional root slices of 0.7 mm were produced and stored for 24 h at 37° C before being submitted to push-out bond strength. Results: The mean and standard deviation values of dislocation resistance were GBisCem: 1.12 (± 0.23) MPa, GOneStep±C&B: 0.81 (± 0.31) MPa, GAllBond±C&B: 0.98 (± 0.14) MPa, and GAllBondSE±C&B: 1.57 (± 0.04) MPa. GAllBondSE±C&B showed significantly higher values of dislocation resistance than the other groups. Conclusions: Based on this study design, it may be concluded that adhesion strategies showed different results of quartz post dislocation resistance. Simplified adhesive system with sodium benzene sulphinate incorporation provided superior dislocation resistance.